OWNERSHIP STRUCTURE ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE IN INDONESIA - JUSTIN GEMA PRASETIO; ASTRID RUDYANTO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
The objective of this research is to find empirical evidence about the effect of ownership structure on corporate social responsibility disclosure. This research uses non-financial companies that consistently listed in Indonesia Stock Exchange from the year 2013 to 2017. Samples are obtained using purposive sampling method, in which 62 companies listed meet the sampling criteria; resulting 310 data available are taken as sample. Multiple linear regression and hypothesis test are used as data analysis method of this research. This research result shows that managerial ownership positively affects corporate social responsibility disclosure, while other ownerships (foreign ownership, institutional ownership and government ownership) have no effect on corporate social responsibility disclosure. The result indicates that reducing agency problem with increased managerial ownership is effective on increasing corporate social responsibility disclosure in Indonesia.